Factors correlated with volleyball spike velocity - Forthomme, B.; Croisier, J.-L.; Ciccarone, G.; Crielaard, J.-M.; Cloes, M. (The American Journal of Sports Medicine, 2005)
Background: Spike effectiveness represents a determining element in volleyball. To compete at a high level, the player must, in particular, produce a spike characterized by a high ball velocity.